Comparative analysis of bacterial and fungal communities in two dairy parlors through the use of pyrosequencing, riboprinting, culture techniques, and microscopic analysis - VanDyke-Gonnerman, Amanda L., author; Reynolds, Stephen J., advisor; Volckens, John, committee member; Ellis, Robert, committee member (Colorado State University. Libraries, 2013)
The purpose of this study was to compare three different analysis techniques used to characterize and identify bacteria and fungi. Pyrosequencing, culture techniques, and riboprinting were compared for all of the bacterial samples and pyrosequencing; culture techniques; and microscopic analysis was used to compare the fungal samples. SKC BioSamplers were used to take area samples inside two modern dairy parlors from May 2012-January 2013. Four sampling sessions were completed at each dairy parlor. Four biosamplers ran side-by-side (two at a time) for 60 minutes at 12.5 l/min in addition to a lab and a field blank. A novel resuscitation buffer was used to collect and aid recovery of stressed bacteria and fungi. Three types of media were used to select for bacteria and fungi: tryptic soy agar (TSA) with a 5% sodium chloride addition for Gram-positive bacteria; Eosin methylene blue (EMB) for Gram-negative bacteria, and malt extract agar (MEA) with a chloramphenicol addition for fungi. Based on colony morphology, the five most commonly encountered bacteria from both TSA and EMB agar were subcultured and identified through riboprinting. Pyrosequencing was performed directly on the biosampler collection media. The culturable bacterial concentrations and the pyrosequencing bacterial concentrations were within the same order of magnitude, which was unexpected. The culturable bacterial concentrations, with averages of 7500 CFU/m3 and 500 CFU/m3 for TSA and EMB plates respectively, were higher than the concentrations found in previous studies which could be a result of the novel resuscitation buffer that was used as a collection media. Greater microbiome diversity was found through pyrosequencing analysis than the riboprinting analysis. The pyrosequencing data found many genera that include species that are pathogenic, but more work must be done to confirm if pathogenic species were found during sampling at these two dairy parlors. The riboprinting samples were identified on the species and strain level and found Escherichia coli O157:H7 a known pathogen as well as Pseudomonas aeruginosa, an opportunistic pathogen. The culturable fungi concentrations and the pyrosequencing concentrations were within the same order of magnitude, which was also unexpected. The pyrosequencing data had greater diversity than the microscopic analysis for the first two sets of samples that were sent for pyrosequencing. The second set of fungal samples that were sent for pyrosequencing came back as non-detect samples despite the growth of fungi on the agar. From the pyrosequencing data, there were many genera found that have pathogenic species, but more research needs to be conducted to determine the presence of the pathogenic species. There were no pathogenic fungal species found through the microscopic analysis.
Keywords: riboprinting; dairy; pyrosequencing; fungi; bacteria; bioaerosols